The relative age effect in turkish professional soccer - Yunus Arslan; Yusuf Köklü; Utku Alemdaroğlu; Hüseyin Gökçe (Asociación Española de Ciencias del Deporte, 2020)
This study examined the Relative Age Effect (RAE) in Turkish professional soccer. The data on 3435 players (MAge = 25.25, SDAge = 1.16) across 127 professional teams from the four Turkish professional leagues were categorized into relative age quartiles (Q1= Jan-Mar; Q2= Apr-June; Q3= Jul-Sep; Q4= Oct-Dec). Birth data and registration dates were collected through the Turkish Football Federation's official website. This data revealed a greater representation of players (approximately 62%) born between January and June, with statistically significant values for all professional leagues (X2(3)= 303.01; p< 0.01). Similarly, domestic players (X2(3)= 316.77; p< 0.01) and foreign players (X2(3)= 14.59; p< 0.01) born in the Q1 and Q2 zones were more likely to be members of Turkish professional leagues than those born in other zones. The findings of the present study also showed a strong RAE for all playing positions (40.37 ≤ X2(3) ≤ 143.5; p< 0.01). Based on the present data, players born in Q1 and Q2 zones, independently of the league level, position and nationality, seem to have advantages compared to those born in the rest of the year.